Pariwisata di Tengah Pandemi Covid-19: Dampaknya terhadap Lingkungan Pantai Sanur - Ni Wayan Anggreni (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2021)
The aim of this study is to examine the impact of tourism in the midst of the Covid-19 pandemic on the Sanur Beach environment. The data collection method used in this research is the method of observation and documentation. The analytical technique used to achieve the research objectives is descriptive qualitative analysis. The analyzed results are presented using formal and informal techniques. The results show that tourism has a positive and negative impact on the Sanur Beach environment in the midst of the current Covid-19 pandemic. The positive impacts of tourism in the midst of the Covid-19 pandemic on the Sanur beach environment include the availability of wide roads for tourists, a well-organized environment, reduced sea water pollution, clean beaches, and inorganic waste such as plastic, bottles, and the like originating from reduced restaurants and merchants. However, the negative impacts of tourism in the midst of the Covid-19 pandemic on the Sanur beach environment include organic waste such as fallen leaves dominating, air pollution due to burning leaves, and organic waste such as piled leaves.